On identification of anomalies in multidimensional hydrogeochemical data as earthquake precursors - Evgueni A. Haroutunian; Irina A. Safaryan; Hrachya M. Petrosyan; Armine R. Gevorkyan (Изд-во НАН РА)
We consider two nonparametric methods are discussed for identification of anomalies in multidimensional hydrogeochemical data with the goal of forecasting major seismic events. The first method is based on using the threshold copula function aimed at the definition of change moments in the structure of dependencies between the components of a multidimensional vector of observations. The second method is designed to transform multidimensional data to one-dimensional which allows to use rank score tests.
Keywords: Mathematics